Exo-D-Mapps Attenuates Production of Inflammatory Cytokines and Promoted Generation of Immunosuppressive Phenotype in Peripheral Blood Mononuclear Cells - Harrell Carl Randall (Serbian Journal of Experimental and Clinical Research, 2022)
Mesenchymal stem cells (MSCs) produce immunomodulatory factors that regulate production of cytokines and chemokines in immune cells affecting their functional properties. Administration of MSCs-sourced secretome, including MSC-derived conditioned medium (MSC-CM) and MSC-derived exosomes (MSC-Exos), showed beneficial effects similar to those observed after transplantation of MSCs. Due to their nano-size dimension, MSC-Exos easily penetrate through the tissue and in paracrine and endocrine manner, may deliver MSC-sourced factors to the target immune cells modulating their function. MSCs derived from amniotic fluid (AF-MSCs) had superior cell biological properties than MSCs derived from bone marrow. We recently developed “Exosomes Derived Multiple Allogeneic Proteins Paracrine Signaling (Exo-d-MAPPS)”, a biological product in which the activity is based on AF-MSC-derived Exos capable to deliver immunomodulatory molecules and growth factors to the target cells. Herewith, we analyzed immunosuppressive capacity of Exo-d-MAPPS against human peripheral blood mononuclear cells (pbMNCs) and demonstrated that Exo-d-MAPPS efficiently suppressed generation of inflammatory phenotype in activated pbMNCs. Exo-d-MAPPS attenuated production of inflammatory cytokines and promoted generation of immunosuppressive phenotype in Lipopolysaccharide-primed pbMNCs. Exo-d-MAPPS treatment reduced expansion of inflammatory Th1 and Th17 cells and promoted generation of immunosuppressive T regulatory cells in the population of Concanavalin A-primed pbMNCs. Similarly, Exod-MAPPS treatment suppressed pro-inflammatory and promoted anti-inflammatory properties of α-GalCer-primed pbMNCs. In summing up, due to its capacity for suppression of activated pbMNCs, Exo-d-MAPPS should be further explored in animal models of acute and chronic inflammatory diseases as a potentially new remedy for the attenuation of detrimental immune response.